On the surface roughness properties of fly ash-based geopolymer mortars with teff straw ash from the image analysis viewpoint - Tajebe Bezabih; David Sinkhonde; Derrick Mirindi (Green Technologies and Sustainability)
Fly ash (FA)-based geopolymer mortar is being considered for sustainability since it enjoys peculiar properties such as high mechanical properties and environmental benefits. However, the high curing temperatures of FA-based geopolymer mortar play a complex role in its outstanding mechanical behaviour thereby requiring other precursors, such as teff straw ash (TSA). In this study, we develop surface roughness properties of FA-based geopolymer mortars with TSA, where the ambient temperature is used for curing. The surface roughness characteristics of the FA-based geopolymer mortars with TSA exploit the surface roughness simulations from Gwyddion and the approach is demonstrated here in the contexts of spatial, hybrid and amplitude roughness parameters. The results show that some roughness parameters, including Raand Rqvalues for FA-based geopolymer mortars with TSA, exhibit significant decreasing trends as the TSA contents increase. However, in comparison with the CA specimens (ambient temperature curing) and CE specimens (elevated temperature curing), the trends among the majority of the roughness parameters for FA-based geopolymer mortars with TSA turn out not to be very good probably due to changes in the internal structures of the mortars. Moreover, without the kurtosis values (Rku) of less than 3, it is easy to demonstrate that all the profiles of the investigated specimens reflect sharp valleys and peaks. The findings of surface roughness properties allow one to grasp the roughness parameters of FA-based geopolymer mortars with TSA. The approach for generating surface roughness properties of FA-based geopolymer mortars with TSA offers significant quantitative and qualitative information required for the bonding of mortar layers.